Vibrio alginolyticus Survives From Ofloxacin Stress by Metabolic Adjustment - Yin, Yue; Yin, Yuanpan; Yang, Hao; Chen, Zhuanggui; Zheng, Jun; Peng, Bo (Frontiers in Microbiology, 2022)
Antibiotic-resistant Vibrio alginolyticus become a worldwide challenge threatening both of human health and food safety. The approach in managing such infection is largely absent, despite the mechanisms of antibiotic resistance have been extensively investigated. Metabolic modulation has been documented to be a novel approach in improving antibiotic efficacy. In this study, we characterize the metabolic signature of V. alginolyticus exposed to 0.3 μg/mL or 0.5 μg/mL of ofloxacin (OFX). By profiling the metabolome, we find that bacteria treated by the two different concentrations of OFX generate different metabolic signatures. While part of these metabolites was shared by both of groups, the other metabolites represent their own signatures. The pathway enrichment analysis demonstrates that the pyruvate cycle is disrupted in bacteria treated by the 0.3 μg/mL OFX as compared to those by the 0.5 μg/mL. Importantly, the disruption of pyruvate cycle confers bacteria capability to survive under 0.5 μg/mL of antibiotic stress. Further analysis identifies that the fatty acid biosynthesis is elevated in bacteria treated by 0.3 μg/mL OFX, and inhibition on fatty acid completely prevents the bacteria from survival even under such dose of antibiotic stress. Our study suggest that bacteria adapt to antibiotic stress by modulating the metabolic flux for survival, which could be targeted to increase antibiotic efficacy.